Optimization of solid circualtion rate in compartmented fluidized bed gasifier for power generation - Chok, Vui; Wee, Siaw; Gorin, Alexander; Chua, Han; Mohd. Ariffin, M.Z.; Yan, H.M. (American Institute of Physics, 2008)
The present paper reports the optimization of solid circulation rate (SCR) in Compartmented Fluidized Bed Gasifier (CFBG), an indirectly heated fluidized bed that incorporates two sets of v-valves and risers to control the solid circulation across the two compartments, i.e. combustor and gasifier of a pilot plant scale (the height and ID are 1.8m and 0.66m respectively). Sand was used as inert fluidized by air. Four operating variables were studied i.e. bed height, riser, v-valve and main bed flowrate. Based on (2)*4 full factorial design of experiment in Yates' algorithm, at confidence level >=95%, ANOVA analysis showed that there are 6 important effects. The steepest ascent method was applied on linear regression generated from these effects to design the subsequent optimization experiments. The optimum values of SCR have been estimated for both low and high bed level at specific operating parameters.